Zaznavanje in prikazovanje 3D slik - Ravnik, Jan (Matrika, 2014)
This paper describes the basics of human perception of three dimensions and represents an overview of different ways of sensing and displaying 3D images, as well as their general usage for different applications. Some of the most used techniques are described more detailed with advantages and disadvantages over other similar techniques.
Keywords: autostereoscopy; avtostereoskopija; holografija; holography; integral imaging; integralsko slikanje; stereoscopy; stereoskopija